(untitled) (Texas Journal of Philology, Culture and History, 2021)
Today, learning languages are becoming common all over the world. It is worth Studying not only one foreign language, but also 3 and more languages in order to be successful person in every career/field. For this reason, this article is devoted to consideration for transference in the context of trilingualism.